Bisnaphthalimidopropyl diaminodicyclohexylmethane induces DNA damage and repair instability in triple negative breast cancer cells via p21 expression. (5th December 2015) - Barron, Gemma A.; Goua, Marie; Kuraoka, Isao; Bermano, Giovanna; Iwai, Shigenori; Kong Thoo Lin, Paul
Abstract: Bisnaphthalimidopropyl diaminodicyclohexylmethane (BNIPDaCHM) bisintercalates to DNA and is a potential anti-cancer therapeutic. In an attempt to elucidate the mechanism(s) underlying the potential of BNIPDaCHM; earlier work was extended to investigate its effect on DNA damage and repair as well as cell cycle modulation, in a triple negative breast cancer (TNBC) cell line in vitro . BNIPDaCHM significantly decreased cell viability in a concentration (≥5 μM) and time (≥24 h) dependent manner. The mechanism of this growth inhibition involved alterations to cell cycle progression, an increase in the sub-G1 population and changes to plasma membrane integrity/permeability observed by flow cytometry and fluorescence microscopy with acridine orange/ethidium bromide staining. Using single cell gel electrophoresis (Comet assay) and fluorescence microscopy to detect γ-H2AX-foci expression; it was found that after 4 h, ≥ 0.1 μM BNIPDaCHM treatment-induced significant DNA double strand breaks (DSBs). Moreover, exposure to a non-genotoxic concentration of BNIPDaCHM induced a significant decrease in the repair of oxidative DNA strand breaks induced by hydrogen peroxide. Also, BNIPDaCHM-treatment induced a significant time dependent increase in p21 Waf/Cip1 mRNA expression but, did not alter p53 mRNA expression. In conclusion, BNIPDaCHM treatment in MDA-MB-231 cells was associated with a significant induction of DNA DSBs and inhibition of DNA repair at non-genotoxic concentrations via p53-independent expression of p21 Waf1/Cip1 . The latter may be a consequence of novel interactions between BNIPDaCHM and MDA-MB-231 cells which adds to the spectrum of therapeutically relevant activities that may be exploited in the future design and development of naphthalimide-based therapeutics. Highlights: BNIPDaCHM induced a time- and concentration-dependent decrease to cell viability. BNIPDaCHM altered cell cycle progression, increased cells in the sub-G1 population and changed plasma membrane permeability. BNIPDaCHM significantly induced DNA double strand breaks and inhibited DNA repair at non-genotoxic concentrations. BNIPDaCHM induced a significant time-dependent p53-independent expression of p21 Waf/Cip1 leading to cell death.